Challenges Affecting the Effectiveness of Students’ Coping Strategies: Evidence from Darkhan-Uul Province University Students (Journal of Interdisciplinary Insights, 2025)
As global interconnectedness increases, societal complexity is intensifying. The expanding use of digital technologies has contributed to rising individualism among students and to challenges such as reduced concentration, impatience, loneliness, vulnerability to depression, and weakened short-term memory. These trends underscore the need for educators to collaborate with learners, support mutual learning, and address individual differences. Developing instructional approaches that align with students’ cognitive processes enables them to identify personal challenges, learn from them, and strengthen their capacity to overcome difficulties. Against this background, the purpose of the present study is to enhance students’ coping strategies and to inform the development of a curriculum for a “Stress Management” course. A total of 313 students from the University of Darkhan-Uul Province participated in the study. Coping strategies were assessed using the Brief-COPE psycho-diagnostic instrument, a widely used, reliable, and valid measure of coping styles. Results indicated that students most frequently used Problem-Focused Coping (M = 2.84), followed by Emotion-Focused Coping (M = 2.60), and Avoidant Coping (M = 2.50, 62). These findings suggest that students primarily rely on realistic, problem-oriented strategies, with moderate use of emotional regulation and lower reliance on avoidance-based behaviors, including distraction or risk-prone coping. Overall, the results provide an empirical foundation for designing evidence-based stress management curricula that support students’ psychological well-being and adaptive coping skills.